Comparative child mental health and academic outcomes after primary school teachers deliver task-shifted mental health care in India - Priscilla Giri; Molly M. Lamb; Venessa C. Fuentes; Arpana Thapa; Surekha Bhattarai; Choden Dukpa; Catherine C. Shrestha; Setareh Ekhteraei; Juliana L. Vanderburg; Breanna Windsor; Abhishek K. Rauniyar; Karen Hampanda; et al. (Discover Mental Health)
Abstract Teachers are promising lay counselors but have limited time for traditional therapy. To viably leverage teachers to deliver care, we developed Teachers Leading the Frontlines (Tealeaf), where teachers deliver a novel therapy, “education as mental health therapy” (Ed-MH); measures are an extension of classroom management, not an added task. We investigated whether Tealeaf teachers improved child mental health symptoms and academic achievement versus teachers delivering an enhanced usual care (EUC) comparator, Responding to Students' Emotions through Education (RE-SEED), a truncated version of Tealeaf. We conducted a pragmatic, mixed methods, post hoc analysis using data from 2019 of an open trial of Tealeaf running in parallel with the all-EUC first step of a stepped wedge cluster randomized controlled trial (SW-CRCT). We compared postintervention child mental health symptom scores and academic achievement. Semi-structured interviews and focus groups were analyzed using inductive content analyses. Tealeaf teachers observed lower mental health symptom severity (n = 23 children in Tealeaf, n = 104 in RE-SEED; Cohen’s d = 0.70; p = 0.024). Students in Tealeaf (n = 26, n = 183 in RE-SEED) performed better in math (d = 0.63; p = 0.0006) and reading (d = 0.83; p = 0.001). Caregivers of children in RE-SEED (n = 177), the comparator condition, reported lower severity of overall mental health difficulties and internalizing difficulties for their children compared to caregivers’ reports of their children in Tealeaf (n = 25). Tealeaf teachers displayed a greater depth in mental health understanding in mixed methods findings. Evidence supports teachers' potential to improve child mental health and academics in school while underscoring the need for additional home‐based supports. Tealeaf Clinical Trials Registry—India (CTRI) Reg. No. CTRI/2018/01/011471, Ref. No. REF/2017/11/015895; date of registration 2018-01-01. RE-SEED TRN NCT04723277; date of registration 2021-01-25.